Visual symbolism in 2D animated film on the traumatic impact of child abuse - Alisa Arindhani; Devi Kurniawati Homan; Jonata Witabora (Jurnal Desain, 2025)
Sexual violence remains a critical and pervasive issue in Indonesian society, affecting victims across diverse demographics and social backgrounds. Prepators are often individuals in positions of trust, such as family members, educators, or religious leaders, highlighting the deeply entrenched nature of the problem. Using a qualitative method, this paper tries to investigate the phenomenon by exploring the use of animation as a powerful and underutilized medium in Indonesia for addressing complex and taboo social issues. Animation offers artists a platform to navigate sensitive topics without the constraints of realism. In a society where discussion of sexual abuse is often silenced due to cultural aspects, animation can serve as a bridge that connects viewers emotionally and intellectually to the experience of survivors. By implementing metaphor, stylization, symbolism, animated narratives can bypass societal resistance and foster empathy dan dialogue. Specifically, this paper analyzes the 2D animated short film “Next Time”, focusing on the visual symbols used to convey the emotional and psychological impact of sexual abuse. The finding emphasizes that an interdisciplinary approach combining sociological insight and artistic expression can be a powerful tool for social change.